Pemenuhan Akses Penyandang Disabilitas Anak terhadap Hak Atas Pendidikan - Louis (VYAVAHARA DUTA, 2024)
This article examines the fulfillment of access for children with disabilities to the right to education. In Indonesia, people with disabilities still have problems, from inadequate fulfillment of the rights and obligations of people with disabilities to negative stigma from society related to people with disabilities which is formed from various aspects. The research method used is normative juridical with a descriptive research type in the nature of a literature study. The type of data used is secondary data